2016
DOI: 10.14202/vetworld.2016.705-709
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of fluoroquinolone-resistant Escherichia coli associated with bovine mastitis in India

Abstract: Aim:The present study was undertaken to characterize the mutation in gyrA (DNA gyrase) and parC (topoisomerase IV) genes responsible for fluoroquinolone resistance in Escherichia coli isolates associated with the bovine mastitis.Materials and Methods:A total of 92 milk samples from bovine mastitis cases were sampled in and around Puducherry (Southern India). Among these samples, 30 isolates were bacteriologically characterized as E. coli. Minimum inhibitory concentrations (MIC) of fluoroquinolones of these 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Isolates from poultry and rooks that displayed clinical levels of ciprofloxacin resistance linked to single or double mutations in gyrA and parC were found in our study. Strains of various animal origin with these types of mutations have been recently found worldwide (Sáenz et al, 2003; Liu et al, 2012; Castillo et al, 2013; Johnning et al, 2015; Balakrishnan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Isolates from poultry and rooks that displayed clinical levels of ciprofloxacin resistance linked to single or double mutations in gyrA and parC were found in our study. Strains of various animal origin with these types of mutations have been recently found worldwide (Sáenz et al, 2003; Liu et al, 2012; Castillo et al, 2013; Johnning et al, 2015; Balakrishnan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It is also commonly used for water treatment in poultry houses, thus making sulfonamides as a major environment pollutant in the poultry house effluents [ 54 ]. Balakrishnan et al , 2016 [ 30 ] isolated fluoroquinolones resistant E. coli isolates of animal origin from Puducherry. In contrast, Ramatla et al, 2022 [ 55 ] found a higher percentage of qnrA and tet gene resistance in rodents in South Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Representative samples from the isolates tested to have AMR genes were used to carry out the antibiotic sensitivity test (ABST) using the antibiotic impregnated discs procured from Hi Media Laboratories, India. ABST was carried out following the standard procedure [ 30 ]. Methicillin resistance in S. aureus was confirmed using Methicillin (M) 5 μg.…”
Section: Methodsmentioning
confidence: 99%
“…Although antibiotics are an optimal treatment for bovine clinical mastitis [10][11][12][13], the massive use of antimicrobial drugs has led to the emergence of drug-resistant strains of E. coli, thus making effective prevention and treatment of mastitis extremely difficult [9,[14][15][16][17][18]. In the context of the current advocacy of resistance reduction initiatives, methods using biological agents against mastitis are being developed, including phage therapy, antimicrobial therapy, antibody therapy, nonspecific immune boosting prophylaxis and vaccine prophylaxis.…”
Section: Introductionmentioning
confidence: 99%